Targless indoor positioning and object tracking using a wireless sensor network - Kho, Y. H.; Ellis, G. A. (Nazarbayev University, 2013)
With the proliferation of wireless sensor network of which the Wi-Fi access points are part of, it is proposed that the project shall look into using the existing backbone infrastructure of Wi-Fi modems to double-function as sensors for the proposed indoor positioning system. To do this, fundamentally the received signal strength of transmitted RF wave needs to be measured and tracked in real time. Relevant hardware needs to be selected and /or designed, and tracking algorithm(s) needs to be designed.
Keywords: first research week; indoor positioning systems